2024
DOI: 10.1123/ssj.2022-0121
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing, Challenging, and Negotiating Sex/Gender in Sport: U.S. Public Opinion About Transgender Athletes’ Rights, Rights for Athletes With Varied Sex Characteristics, Sex Testing, and Gender Segregation

Abstract: Using data from the National Sports and Society Survey (N = 3,993), this study considers U.S. public opinion about transgender athletes’ rights, rights for athletes with varied sex characteristics, sex testing, and gender segregation in sports. Social structural location, social group, and ideological characteristics are examined as predictors of these opinions. Results indicated that most U.S. adults seem to support transgender athletes’ rights and rights for athletes with varied sex characteristics and oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The reported attitudes of cisgender respondents towards transgender athletes within this research is also somewhat affirmed by the mostly positive experiences reported for gender minorities in cycling, as well as supporting recent findings in the USA regarding positive public attitudes towards trans athletes (Knoester et al, 2023). There were also limited reports of experiencing physical and/or verbal hostility with intent to harm due to being transgender.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reported attitudes of cisgender respondents towards transgender athletes within this research is also somewhat affirmed by the mostly positive experiences reported for gender minorities in cycling, as well as supporting recent findings in the USA regarding positive public attitudes towards trans athletes (Knoester et al, 2023). There were also limited reports of experiencing physical and/or verbal hostility with intent to harm due to being transgender.…”
Section: Discussionsupporting
confidence: 89%
“…Alongside recent data from the USA (Knoester et al, 2023), these findings suggest that the ‘culture war’ around trans inclusion in sport whereby much cultural hysteria around trans women is purported in the media may not be reflective of people's attitudes and opinions on the topic, which seem to be more aligned to those expected within a culture of inclusion. Whilst further research with a larger representation of trans cyclists is required for a more comprehensive understanding of this area in cycling, particularly in light of the current prominence of cultural awareness and discussions of trans participation in sport, this data stands out as noteworthy.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Persistent condemnations of Colin Kaepernick and other athlete activists by Republican politicians even in the absence of any meaningful protest activity are another. Still others include criticisms of the Biden administration for negotiating the release from Russian prison of WNBA Brittney Griner release (Keaton et al, 2023); of sports figures now turned conservative politicians ranging from Kelley Loeffler and Hershel Walker in Georgia to Tommie Tuberville in Alabama; the New College in Florida creating an interscholastic athletic program for the explicit purpose of combating "wokeness" and "political correctness" on campus; and most recently and extensively, the wave of attacks on and moral panics about trans athletes (Baeth & Goorevich, 2022;Fischer, 2023;Knoester et al, 2023;Sharrow, 2021). 3 There are at least three aspects of Right-wing engagements with sport that need to be highlighted.…”
Section: Right-wing Populist Engagements With Sportmentioning
confidence: 99%